2007
DOI: 10.1021/bp060292t
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CD40 Expression and Enhancement of Monoclonal Antibody Production on Murine B Cell Hybridomas by Cross‐Linking of IgG Receptors

Abstract: The 55-6 murine B cell hybridoma line not constitutively expressing CD40 was treated with increasing amounts of intact anti-mouse surface immunoglobulin G antibody (anti-mIgG) either not preincubated or preincubated for 48 h with lipopolysaccharide (LPS). In vitro, cross-linking of surface immunoglobulin G (sIgG) with the whole molecule of anti-IgG antibodies induced the expression of CD69, CD40, and CD19 surface antigens on 55-6 cells. The effect of sIgG ligation was dose-dependent, and preincubation with LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In previous experiments with the 55-6 hybridoma cell line (16) we demonstrated that both CD40 expression and surface IgG content, as detected with immunofluorescent techniques, were maximum during the G1 cell cycle phase on cells stimulated with anti-mIgG. Moreover, a correlation between the specific antibody secretion rate and surface IgG content was observed.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…In previous experiments with the 55-6 hybridoma cell line (16) we demonstrated that both CD40 expression and surface IgG content, as detected with immunofluorescent techniques, were maximum during the G1 cell cycle phase on cells stimulated with anti-mIgG. Moreover, a correlation between the specific antibody secretion rate and surface IgG content was observed.…”
Section: Introductionmentioning
confidence: 55%
“…The cell line used, a mouse-mouse B cell hybridoma, designated 55-6 (ATCC: CRL-2156), produces IgG2a monoclonal antibodies to human immunodeficiency virus (HIV) glycoprotein 120 (gp120). The cells were grown in static T-culture flasks in the medium previously described by Martín-López et al, (16).…”
Section: Methodsmentioning
confidence: 99%
“…These data showed that LPS and antimIgG, which are widely considered as activatingagent of B cells (Kearney and Lawton 1975;Klaus et al 1984;Lenschow et al 1991;Oliver et al 1999), may trigger the same metabolic routes in hybridoma as in B cells to increase their proliferation and mAbs production. Moreover, this stimulatory effect of LPS and anti-mIgG was higher during G1 phase of the cell cycle (Martín-López et al 2007b).…”
Section: Discussionmentioning
confidence: 89%
“…The cells were grown in static T-culture flasks in the medium previously described (Martín-López et al 2007b). …”
Section: Cell Line and Cell Maintenancementioning
confidence: 99%
See 1 more Smart Citation